(untitled) (International Journal of Environmental Sciences, 2025)
Plastics have become an indispensable part of modern life due to their versatility, durability, and cost-effectiveness. However, their widespread use has led to severe environmental consequences, primarily due to their persistence in natural ecosystems. Conventional fossil-fuel-based plastics degrade very slowly, contributing to pollution in terrestrial and marine environments and threatening biodiversity. As a result, there is a growing global demand for sustainable alternatives such as biodegradable plastics, which are designed to decompose naturally and return carbon to the environment through microbial action. Despite their potential, biodegradable plastics have not yet achieved large-scale replacement of conventional plastics, even after more than a decade of commercial availability. This paper critically reviews the current landscape of biodegradable plastics, exploring why they fall short in contributing to a truly circular economy. It discusses key challenges including limited material performance, inconsistent degradation across environments, lack of standardized testing protocols, restricted application domains, and inefficient waste management systems. To address these barriers, interdisciplinary collaboration is essential—spanning materials science, industry stakeholders, policymakers, and waste management authorities. The article also highlights recent innovations and emerging research in plastic biodegradation, along with the growing role of machine learning in accurately assessing biodegradability. Such technologies can facilitate targeted recycling, improve product design, and support regulatory compliance. By examining both the limitations and the future prospects, this work aims to provide a comprehensive perspective on enabling sustainable plastic solutions.